Factors that influence the adoption of Balanced Scorecard (BSC) on a cooperative agro industry: a study based on innovation diffusion theory - Lopes, Antonio Carlos Vaz (2015)
The objective of this work is to understand the process of adoption, implementation, and utilization of an organizational innovation, in this case BSC in a major cooperative Brazilian agro-industrial company using the theory of diffusion of innovation (TDI). The study the qualitative research approach was utilized, to allow a detailed the exploration the experiences of the participants, in the process of adoption of innovation much like the effects of BSC on organization, semi-structured interviews with the main actors involved in the decision-making process of adoption and implementation of this innovation. The results of the research showed that the adoption of BSC in the company was mainly motivated by the search for efficiency in relation to the system used to evaluate performance, translation, communication, implementation and strategy management. The decision for BSC was taken by high administration who participated in the process and provided all the necessary so that the same would be part of the company’s routine. The internal team elaborated and implemented BSC using participative approach involving managers at all organizational levels who acted as promoting agents of the change. We conclude that the attributes of the innovation: relative advantage, ease of use and compatibility were the main influencers of the adoption of BSC. In this way, the theory of diffusion of innovation can be used to aid in the decision process of BSC.